1984
DOI: 10.1128/iai.46.3.845-849.1984
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation and induction of macrophage cytotoxicity by purified polysaccharide fractions from the plant Echinacea purpurea

Abstract: Purified polysaccharides (EPS) prepared from the plant Echinacea purpurea are shown to strongly activate macrophages. Macrophages activated with these substances develop pronounced extracellular cytotoxicity against tumor targets. The activation is brought about by EPS alone and is independent of any cooperative effect with lymphocytes. Also the production and secretion of oxygen radicals and interleukin 1 by macrophages is increased after activation with EPS. Cells of the macrophages lineage seem to be the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(71 citation statements)
references
References 15 publications
2
68
0
1
Order By: Relevance
“…Other studies have reported that purified polysaccharides from E. purpurea induced macrophage production of IL-1 (Stimpel et al 1984), and that a polysaccharide arabinogalactan isolated from plant cell cultures of E. purpurea induced TNF-and interferon-2 production by murine macrophages (Luettig et al 1989). Polysaccharides obtained from plant cell cultures of E. purpurea have also been shown previously to have immunological activity in-vitro .…”
Section: Immunomodulatory Activitymentioning
confidence: 89%
“…Other studies have reported that purified polysaccharides from E. purpurea induced macrophage production of IL-1 (Stimpel et al 1984), and that a polysaccharide arabinogalactan isolated from plant cell cultures of E. purpurea induced TNF-and interferon-2 production by murine macrophages (Luettig et al 1989). Polysaccharides obtained from plant cell cultures of E. purpurea have also been shown previously to have immunological activity in-vitro .…”
Section: Immunomodulatory Activitymentioning
confidence: 89%
“…In contrast, the alkamides of E. angustofolia and E. purpurea exhibit antiinflammatory properties (Muller-Jakic et al, 1994). Thus, several substances found in Echinacea species could potentially affect common cold symptoms by modulation (either enhancement or suppression) of the host immune response (Stimpel et al, 1984;Cheminat et al, 1988;Bodinet and Buescher, 1991;Burger et al, 1997;See et al, 1997). The observation that echinacoside and cichoric acid are free radical scavengers and can protect against free radical induced injury (Facino et al, 1995) is also of interest in light of evidence that oxidative stress may play a role in virus-induced elaboration of IL-8 (Biagioli et al, 1998;Kaul et al, 2000).…”
Section: Echinaceamentioning
confidence: 99%
“…E. purpurea extracts or its puri® ed polysaccharides, used in-vitro or in-vivo, have been shown to activate human and murine phagocytes. These eOE ects include an increase in phagocytosis, chemotaxis, oxidative burst and macrophage cytokine release (Stimpel et al 1984 ;Wagner et al 1988 ;Gaisbauer et al 1990). Studies in the 1980s showed an anti-in¯ammatory eOE ect after topical application of the polysaccharide fraction derived from E. angustifolia root (Tubaro et al 1987 ;Tragni et al 1988).…”
Section: Introductionmentioning
confidence: 99%